2019
DOI: 10.1073/pnas.1912488116
|View full text |Cite
|
Sign up to set email alerts
|

Postdocs’ lab engagement predicts trajectories of PhD students’ skill development

Abstract: The doctoral advisor—typically the principal investigator (PI)—is often characterized as a singular or primary mentor who guides students using a cognitive apprenticeship model. Alternatively, the “cascading mentorship” model describes the members of laboratories or research groups receiving mentorship from more senior laboratory members and providing it to more junior members (i.e., PIs mentor postdocs, postdocs mentor senior graduate students, senior students mentor junior students, etc.). Here we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 24 publications
1
66
0
1
Order By: Relevance
“…Although engagement represents a healthy and positive state of well-being (Feldon et al, 2019), engaged employees need to mobilize resources to face job demands, giving rise to a state of activation-tension. Glucocorticoids, among other mediators, participate in an orchestrated manner in this state.…”
Section: Engagement and Cortisolmentioning
confidence: 99%
“…Although engagement represents a healthy and positive state of well-being (Feldon et al, 2019), engaged employees need to mobilize resources to face job demands, giving rise to a state of activation-tension. Glucocorticoids, among other mediators, participate in an orchestrated manner in this state.…”
Section: Engagement and Cortisolmentioning
confidence: 99%
“…One of the central roles played by postdocs is their vital role as mentors of more junior lab members [10]. Working remotely doesn't mean postdocs can't participate in lab discussions, build lab community, or provide direct mentorship to junior lab members.…”
Section: Rule 6: Remote Postdocs Are Full Members Of the Labmentioning
confidence: 99%
“…The goal is to empower postdocs to be active participants in their mentoring relationships by emphasizing the mentees' contributions in shaping more productive interactions that then can be built upon to develop their own skills as a future mentor. A more recent study reported a positive link between students' skill development trajectory and the active engagement of postdoctoral researchers in lab discussions, although postdocs typically have no formal mentor role [15] and little formal mentorship training [16]. Thus, further examination of the impact of exposure to mentor competencies on postdocs' personal and professional career development via the validated but under-utilized "Mentoring-Up" training program is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…improve retention in academia [ 27 ]. More recent studies have shown effective mentorship is increasingly correlated with enhanced mentee productivity, persistence, self-efficacy, career satisfaction and success [ 15 , 16 ]. As a result of these demonstrated positive outcomes, research mentor training, with a focus on mentor facilitator training at the faculty level to promote dissemination and implementation broadly, has increased [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%